THE POTENTIAL OF ONLINE WRITING TOOLS FOR EFL UNIVERSITY STUDENTS DURING THE COVID-19 PANDEMIC - Fitri Handayani; Nurma Dhona Handayani (English Study Program University of Pasir Pengaraian, 2020)
This study aims to give an overview of potential online writing tools that can be used in teaching writing for EFL university students during the COVID-19 pandemic. This study was a literature review. It explicates online writing tools and reviews previous research exploring the use of these applications for teaching writing. The data was obtained from articles in online academic journals. There were three databases and sites used in finding the articles; Science Direct, Google Scholar, and Research gate. The result shows that there are three potential online writing toolsapplicable for EFL university students in learning writing from home namely Paragraph Punch, Pro-Writing Aid, and Edmodo. Finally, some suggestions are also offered for lecturers and students regarding the use of online writing tools in teaching writing.